Self-assembled monolayers of cyclic aliphatic thiols and their reaction toward electron irradiation - Waske, Prashant Ankushrao; Meyerbröker, Nikolaus; Eck, Wolfgang; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2012)
We investigated an old dogma, namely, that aromatic self-assembled monolayers (SAMs) are cross-linked and stabilized by irradiation with electrons, whereas aliphatic SAMs on the same substrate are degraded under the same conditions. To this end, we prepared SAMs of novel cycloaliphatic molecules (4-cyclohexylcyclohexanethiols, CCHT) on Au(111) surfaces and studied their response to electron irradiation. The CCHT monolayers demonstrated a comparably low extent of molecular defragmentation and damage of the headgroup-substrate interface. This was explained by the dominance of irradiation-induced cross-linking over defragmentation and desorption events, which was additionally supported by the negative resist performance of the CCHT films in the framework of electron beam lithography. This behavior is distinctly different from SAMs of linear aliphatic molecules, which become severely damaged at comparably low irradiation doses and exhibit the positive resist performance. It is, however, similar to the behavior of aromatic monolayers, which underlines the role of the cyclic structure in the balance of cross-linking and defragmentation in monomolecular films.